Crosstalk of cold and gibberellin effects on bolting and flowering in flowering Chinese cabbage - Shi-wei SONG; Yu-ling LEI; Xin-min HUANG; Wei SU; Ri-yuan CHEN; Yan-wei HAO (Journal of Integrative Agriculture, 2019)
The flower stalk is the product organ of flowering Chinese cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee), which is cultivated extensively in South China. Flower stalk formation and development, including bolting and flowering, determine the yield of flowering Chinese cabbage; however, the bolting and flowering mechanisms remain to be explored. To elucidate these processes, we studied the effects of low-temperature and gibberellin (GA) treatments, and their interaction, on stem elongation, bolting time, flowering time, hormone content, and cell morphology in stem of flowering Chinese cabbage. The results showed that both cold and GA treatments accelerated bolting time, stem elongation, and flowering time. Moreover, cold and GA cotreated plants displayed additive positive effects. In addition, cold treatments increased the GA, indole-3-acetic acid, and cytokinin contents and altered cell size in the shoot apices of flowering Chinese cabbage. Treatment with uniconazole, a GA synthesis inhibitor, strongly delayed bolting time, stem elongation, and flowering time, whereas GA, but not cold treatment, rescued this inhibition, indicating that low temperature accelerates bolting and flowering not only through inducing GA in the shoot apices, but also other ways. These results provide a theoretical basis for further dissecting the regulatory mechanism of bolting and flowering in flowering Chinese cabbage.